Effects of physical activity and melatonin on brain‐derived neurotrophic factor and cytokine expression in the cerebellum of high‐fat diet‐fed rats. Issue 3 (18th July 2020) - Sugiyama, Ai; Kato, Hisashi; Takakura, Hisashi; Osawa, Seita; Maeda, Yuki; Izawa, Tetsuya
Abstract: Aims: Obesity suppresses brain‐derived neurotrophic factor (BDNF) expression and increases the expression of pro‐inflammatory cytokines. Herein, we assessed whether exercise training (ET), melatonin administration (MT), or their combination can affect the expressions of BDNF and cytokines in the cerebellum of high‐fat diet (HFD)‐fed rats. Methods: Wistar rats (4 weeks old) were divided into five groups: normal diet (ND)‐fed control (ND‐SED), HFD‐fed control (HFD‐SED), HFD‐fed ET (HFD‐ET), HFD‐fed MT (HFD‐MT), and HFD‐fed MT plus ET (HFD‐ETMT) group. The rats were fed ND or HFD for 17 weeks. Rats were subjected to ET (running on a treadmill) and/or MT (melatonin 5 mg/kg body weight, i.p.) for 9 weeks, 8 weeks after beginning the diet intervention. Changes in BDNF and cytokine expression levels were determined using immunoblotting and cytokine arrays, respectively, 36 hours following the last bout of ET. Results: Neither HFD‐ET nor HFD‐MT rats exhibited enhanced BDNF expression in the cerebellum, but HFD‐ETMT rats had higher level of BDNF expression compared with the others. The expression of TrkB, a BDNF receptor, was higher in HFD‐ETMT rats than in HFD‐ET and HFD‐MT rats. HFD enhanced the expression of interleukin (IL)‐1, IL‐2, and interferon‐γ but reduced the expression of IL‐4, IL‐6, and IL13. ET and ET plus MT counteracted these HFD‐induced changes in cytokine expressions. Conclusion: Exercise in combination with melatonin confers the potential benefits of increasing BDNF and improving HFD‐induced dysregulations of cytokines in the cerebellum. Abstract : High‐fat diet feeding enhanced the expressions of pro‐inflammatory cytokines but reduced those of anti‐inflammatory cytokines in the rat cerebellum. Interestingly, exercise training and exercise in combination with melatonin administration had a reversal effect on high‐fat diet feeding‐induced changes in cytokine expressions.